Heat transfer in turbulent tube flow inserted with loose-fit multi-channel twisted tapes as swirl generators - Suttisak Kunlabud; Varesa Chuwattanakul; Vichan Kongkaitpaiboon; Pitak Promthaisong; Smith Eiamsa-ard (My University, 2017)
Heat transfer and flow behaviors in three-dimensional circular tubes with loose-fit multiple channel twisted tapes were numerically studied. The investigation was examined for Reynolds numbers (Re) ranging from 5000 to 15,000, by using air as testing fluid. Effects of the multiple channel number (N=2,3, and 4), clearance ratio (CR=0.0, 0.025, 0.05, and 0.075) on heat transfer enhancement and flow friction were examined. The numerical results indicate that the tubes with loose-fit multiple channel twisted tapes perform higher heat transfer rates than the plain tube. The enhanced heat transfer rate is escorted with larger pressure drop. Both heat transfer and pressure drop increase with increasing multiple channel number (N) and decreasing clearance ratio (CR). Heat transfer augmented by the loose-fit multiple channel twisted tape with N=4 is higher than those enhanced by the ones with N=2 and 3 by around 9.5–17.8% and 5.8–7.8%, respectively. In addition, the loose-fit multiple channel twisted tapes with clearance ratio of 0.025, 0.05, and 0.075 give lower heat transfer rates than the one with CR=0.0 by around 8.4%, 17.5%, and 28.8%, respectively.
Keywords: Heat transfer enhancement; Heat Transfer Mechanisms